The Impact of Bolsa Família on Schooling - de Brauw, Alan; Gilligan, Daniel O.; Hoddinott, John F.; Roy, Shalini (Elsevier, 2015)
We use longitudinal household data and propensity score weighting methods to assess the impact of Brazil's Bolsa Família conditional cash transfer program on schooling outcomes of children aged 6–17 years. Weak aggregate effects mask considerable heterogeneity. Among girls, the program significantly increases school participation (by 8 percentage points) and grade progression (by 10 percentage points), with large, significant effects across both younger and older girls in rural areas but concentrated among girls aged 15–17 years in urban areas. Few significant impacts are found among boys. We discuss implications and potential mechanisms for differential impacts by sex, age, and location.